PENGARUH PEMASARAN DIGITAL, KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP MINAT NASABAH - Sialagan, Nurmauli; Rostina, Cut Fitri; Sitohang, Sonia Margaretha; Fauzi, Fauzi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine and analyze the effect of digital marketing, service quality, and trust on customer interest in using mobile banking at KCP Bank Sumut Sei Sikambing. This study used a quantitative approach with descriptive quantitative and explanatory research methods. The population consisted of 1,866 customers, with a sample of 100 respondents selected using random sampling techniques and the Slovin formula. Data collection techniques were carried out through questionnaires, interviews, and documentation. Data analysis used multiple linear regression with validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results showed that digital marketing, service quality, and trust had a positive and significant effect on customer interest in using mobile banking, both partially and simultaneously. Trust was found to be the most dominant factor in increasing customer interest in using mobile banking. This study is expected to be used as evaluation material for the bank in improving the quality of digital services and customer trust.